Combination of Balsamin and Flavonoids Induce Apoptotic Effects in Liver and Breast Cancer Cells - Ajji, Parminder K.; Walder, Ken; Puri, Munish (Frontiers in Pharmacology, 2020)
Flavonoids such as naringenin, quercetin and naringin are known to exhibit anticancer properties. In this study, we examined the effects of these flavonoids on cell viability and apoptotic pathways of cancer cells, either singly or in combination with the type 1 ribosome inactivating protein, Balsamin. Treatment with flavonoids (naringenin, quercetin and naringin) plus Balsamin for 48 h reduced HepG2 and MCF-7 cell viability, increased the activation of caspase-3 and -8 and induced apoptosis through up-regulation of pro-apoptotic genes and down-regulation of anti-apoptotic genes. Out of the three flavonoids tested, the Balsamin-Naringenin and Balsamin-Quercetin combinations appeared to be most effective compared to the Balsamin-Naringin combination. Balsamin combined with flavonoids also activated ER-stress mediated apoptosis in breast cancer (MCF-7) cells, which was not activated by Balsamin treatment alone. These experimental results showed that Balsamin combined with flavonoids can reduce HepG2 and MCF-7 cells viability and induce apoptosis, which could be considered as a promising therapeutic approach to sensitize cells to Balsamin treatment, thereby improving its efficacy in breast or liver cancer therapy.